Comparative preclinical evaluation of a microtubule PET tracer with a beta‐amyloid PET tracer in AD mice. (December 2021) - Neelamegam, Ramesh; Zhang, Wei; O'Boyle, Michael; Galvan, Veronica; Fox, Peter T.; Seshadri, Sudha; Kumar, J.S. Dileep
Abstract: Background: Currently available PET tracers used in Alzheimer's disease (AD) have limited utility in prognosis and in revealing reliable clinicopathologic correlations of disease. Therefore, identification and validation of novel biomarkers for AD progression and preclinical disease onset through noninvasive neuroimaging is a top priority in biomedical research. We proposed to target microtubules (MTs) as an imaging target for AD in preclinical, postmortem and clinical studies that support the implication of altered regulation of MTs in AD and positively correlated with neurodegeneration process. Furthermore, MT loss in AD is contributed to a large number of mutated proteins, enzymes, and post‐translational modifications compared to other imaging targets. Therefore, targeting brain MTs may be advantageous, as cumulative loss of MTs is the final common pathway for a variety of biochemical pathologies leading to neurodegeneration in AD. [ 11 C]MPC‐6827 is the pioneer BBB‐penetrating PET tracer available for in vivo imaging of MTs in brain. 1, 2 Herein, we report the comparative binding of [ 11 C]MPC‐6827, and [ 11 C]PiB in Aβ over expressing APP mutated transgenic J20 mice and controls. Method: [ 11 C]MPC‐6827 and [ 11 C]PiB were synthesized using GE Tracerlab FX2 MEI and FX2N modules. Dynamic PET scans were performed for 30 min after tail vein injection of [ 11 C]MPC‐6827 and [ 11 C]PiB in 6‐month‐old J20 mice and littermates (n=4) using a Siemens Focus 220 microPET scanner. Image analyses were performed with Mango software on reconstructed data. Result: PET image analyses show ∼30% of reduced whole brain uptake of [ 11 C]MPC‐6827 in J20 mice whereas, [ 11 C]PiB exhibited modest higher binding (∼10%) in J20 than control mice. Standardized uptake values (SUVs) show similar trend of binding of tracers in prefrontal cortex (PFC) and hippocampus in J20 and control mice. Conclusion: Our preliminary studies show that in J20 mice, binding of the [ 11 C]MPC‐6827 is reduced in whole brain, hippocampus and PFC compared control mice and is inversely correlated with [ 11 C]PiB binding. The effect size of [ 11 C]MPC‐6827 seems higher than [ 11 C]PiB. Therefore, [ 11 C]MPC‐6827 could be used as a PET tracer for human brain imaging of AD and other NDs. Acknowledgement: This work was funded by Center for Biomedical Neuroscience (CBN) 2020‐2021, UT Health San Antonio, Texas, USA.